Quinohemanine, a quinoxalinone-bohemamine hybrid compound from Streptomyces sp. CPCC 200497. (November 2018) - Jiang, Bingya; Zhao, Wei; Li, Shufen; Liu, Hongyu; Yu, Liyan; Niu, Weixiao; He, Hongwei; Wu, Linzhuan
Abstract A quinoxalinone-bohemamine hybrid compound quinohemanine (1 ), together with 1-methyl-2(H )-quinoxalin-2-one (2 ), was isolated fromStreptomyces sp. CPCC 200497, a producer of quinomycins and bohemamines. Compounds1 and2 were purified using standard chromatographic methods, and their structures were defined through interpretation of HRMS, 1D, and 2D NMR data. Both1 and2 displayed moderate cytotoxicity against cancer cell line HepG2.